(3fhGOQ GdabgGA ef CbhGd YdeGA GdCeUGQ GdNGQLjI Yf GdELeGYs - (3CHh HcQ eMeO Hf GdMSf Hf eMeO GdJejej GdLhgQjs ((3CHh GdQVG Hf CHj GdbGSe Hf YHO Gddg Hf YHO GdQMef Hf CHj YeQh s)
(3ChdgG (B:s
(3jHOC HHGH GdJjee s
(3BNQgG (B:s
(3jfJgi HHGH GdbVGA s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs